1991
DOI: 10.1093/jac/27.suppl_c.91
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and bacteriological efficacy, and practical aspects of amikacin given once daily for severe infections

Abstract: In a multicentre non-randomized open prospective study, 124 patients hospitalized in medical infectious disease or intensive care units, with severe community and hospital-acquired bacterial infections were treated with 15 mg/kg body weight amikacin in a once-daily dose given as a 30 min iv infusion, combined with other antibiotics. Infections were bacteriologically proven in 101 patients. The clinical responses showed 83.1% primary success and 83.9% definitive cure predominantly in intensive care patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
36
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 0 publications
3
36
0
3
Order By: Relevance
“…These results are consistent with those obtained by evaluation of a once-daily dosing regimen for gentamicin in neonates (52). They have important clinical implications, as the outcome depends on the maximum concentration in plasma in patients treated with aminoglycosides (2,(35)(36)(37). The higher the maximum concentration, the better the outcome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with those obtained by evaluation of a once-daily dosing regimen for gentamicin in neonates (52). They have important clinical implications, as the outcome depends on the maximum concentration in plasma in patients treated with aminoglycosides (2,(35)(36)(37). The higher the maximum concentration, the better the outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that both the therapeutic response and toxic effects depend on plasma amikacin concentrations. Achieving a therapeutic maximum concentration of amikacin in plasma is associated with a significant decrease in the rate of mortality due to infection in critically ill patients (2,36,37), and a relationship has also been found between the minimum plasma amikacin concentration and renal toxicity (20,49). Interindividual variability in the pharmacokinetics of amikacin may therefore make it difficult to achieve safe and effective treatment.…”
mentioning
confidence: 99%
“…Regarding P. aeruginosa and Enterobacter cloacae, Garraffo et al demonstrated that the length of time for which amikacin levels were main- on May 12, 2018 by guest http://aac.asm.org/ tained above the MICs was an important parameter for bactericidal activity. In bronchial secretions from patients administered amikacin once daily, amikacin levels were above 8 mg/ liter for more than 12 h. Several clinical studies, some including critically ill patients, have shown that once-daily amikacin treatment can be as effective as the usual regimen (3,11,16). In a population of 45 patients with gram-negative bronchopneumonias, once-daily amikacin treatment could achieve a high clinical success rate, above 70%; moreover, Acinetobacter spp.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that an improved outcome in patients with infections by gram-negative infections was directly related to the peak concentration of the aminoglycoside (13,14). For these reasons, a once-daily regimen has been used in clinical practice and, more recently, in critically ill patients (1,11). The influence of hour of administration in such regimens has not been studied in humans.…”
mentioning
confidence: 99%